Simulation of 802.21 Handovers Using ns-2. (27th June 2010) - Marques, Hugo; Ribeiro, José; Marques, Paulo; Rodriguez, Jonathan
Abstract : The new IEEE 802.21 standard specifies link layer intelligence and other related network information to upper layers in order to optimize handovers between networks of different types, such as WiMAX, Wi-Fi, and 3GPP. This paper makes a short description of 802.21 standard, how it is implemented in ns-2, and the signaling used in a handover between WiMAX and Wi-Fi. The paper also proposes a novel and very simple approach to determine the expected number of handovers in an ns-2 simulation and also evaluates the reliability and scalability of ns-2 when simulating 802.21 scenarios with multiple nodes.